If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(k + 11) = 6(k + -5) Reorder the terms: -6(11 + k) = 6(k + -5) (11 * -6 + k * -6) = 6(k + -5) (-66 + -6k) = 6(k + -5) Reorder the terms: -66 + -6k = 6(-5 + k) -66 + -6k = (-5 * 6 + k * 6) -66 + -6k = (-30 + 6k) Solving -66 + -6k = -30 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. -66 + -6k + -6k = -30 + 6k + -6k Combine like terms: -6k + -6k = -12k -66 + -12k = -30 + 6k + -6k Combine like terms: 6k + -6k = 0 -66 + -12k = -30 + 0 -66 + -12k = -30 Add '66' to each side of the equation. -66 + 66 + -12k = -30 + 66 Combine like terms: -66 + 66 = 0 0 + -12k = -30 + 66 -12k = -30 + 66 Combine like terms: -30 + 66 = 36 -12k = 36 Divide each side by '-12'. k = -3 Simplifying k = -3
| x^2+12x=324 | | 4(x+-2)=3(1.5+x) | | 32+32x=-4(-8x+1) | | 6/7s=-1/6 | | (7x+1)+(5x-1)=180 | | -89=-3(-3v+4)-5 | | (x+y)(a+b)=0 | | ax+bx+2=-8 | | 2/8=5/x | | 8(-5m-2)-6m=260 | | 0=-26t^2+44t+5 | | -7x+50=-2x+15 | | 8(5n-2)=-336 | | -4x/ | | (x+y)(x+y)=0 | | (x+y)(x+y)(x+y)=0 | | -4(1-8p)=-100 | | (x+y)(x+y)(x+y)=1 | | 0=-16t+44t+5 | | 83=6(n+3)+7n | | (3x-7)(4x+7)=0 | | y=[x]2+8x | | 2x+16x+5=0 | | x-.17=504.23 | | 2x^2-y^2=41 | | r(-50)=0 | | x-.17x=504.23 | | x-3(10-3x)=100 | | 1=1-x-4x | | 16=1/2h^2 | | x-.24x=465.12 | | 0.06(x^2)+0.15y(30-x)=0.12(8x) |